Associations between Oxidized LDL to LDL Ratio, HDL and Vascular Calcification in the Feet of Hemodialysis Patients - An, Won Suk; Kim, Seong-Eun; Kim, Ki-Hyun; Bae, Hae-Rahn; Rha, Seo-Hee (Journal of Korean medical science, 2009)
Cardiovascular mortality is associated with vascular calcification (VC) in hemodialysis (HD) patients. The present study was designed to find factors related with medial artery calcification on the plain radiography of feet by comparing C-reactive protein (CRP), plasminogen activator inhibitor type 1 (PAI-1) and lipid profile including oxidized low density lipoprotein (ox-LDL) and to elucidate associations among these factors in HD patients. Forty-eight HD patients were recruited for this study. VC in the feet was detected in 18 patients (37.5%) among total patients and 12 patients (85.7%) among diabetic patients. Diabetes, cardiovascular disease (CVD), pulse pressure, ox-LDL/LDL were higher and high density lipoprotein (HDL) was lower in patients with VC than in patients without VC. Negative associations were found between HDL and CRP, PAI-1. PAI-1 had positive association with ox-LDL/LDL. History of CVD was the only determinant of vascular calcification on the plain radiography of feet. Ox-LDL/LDL, HDL, CRP, and PAI-1 were closely related with one another in HD patients. History of CVD is the most important factor associated with the presence of VC and low HDL and relatively high oxidized LDL/LDL ratio may affect VC formation on the plain radiography in the feet of HD patients.